Efektifitas Komunitas Seni sebagai Strategi Promosi di Kedai Kopi Gresiknesia - sastrawati, rosi (Jurnal Mahasiswa Manajemen, 2021)
Background - Increasing an effort or business affects intense competition. One of them is in the coffee shop business in Gresik City. In need of effective promotion strategy to face the competition of the coffee shop. In this research the object to be meticulously is the Gresiknesia coffee shop that makes the art community as a promotional strategy. Using an EPIC model (Emphaty, Persuasion, Impact, Communication), researchers will measure the effectiveness of the art community as a promotional strategy at Gresiknesia coffee shop. Objective - The purpose of this study is to analyze and determine the extent to which the effectiveness of the arts community as a promotional strategy in Gresiknesia coffee shop. Design : The study uses a qualitative approach with qualitative descriptive methods. To measure effectiveness, researchers take data and information from four key informant and two non-key informant through observation and interviews directly with the support of documentation data. Findings - The result of the study was that the art community was instrumental in the promotion at the Gresiknesia coffee shop, because the reason visitors came to Gresiknesia coffee shop was to enjoy the event there in addition to enjoying coffee. In addition to the Gresik people, people outside the city also know the Gresiknesia coffee shop because of the art community. So the strategy used in Gresiknesia coffee shop is already effective if measured using EPIC models. Research implications - This research contributes to marketing management by utilizing art as an added value. Research limitations - The limitation in this study is to measure the effectiveness of marketing strategies only in terms of promotion using the EPIC model.